Research on the Histological Features and Pathological Types of Gastric Adenocarcinoma With Mucinous Differentiation - Meng, Nian-Long; Wang, Yang-kun; Wang, Hai-Li; Zhou, Jun-Ling; Wang, Su-nan (Frontiers in Medicine, 2022)
Objective To discuss the histological features, pathological types, and prognosis of gastric adenocarcinoma with mucinous differentiation. Methods Specimens of 189 cases of gastric adenocarcinoma with mucinous differentiation were collected for detailed histomorphology, immunohistochemistry, fluorescence in situ hybridization, and follow-up. Results In accordance with the morphological and histological structural features of the cancer cells as well as the area ratio of the mucus, gastric adenocarcinoma with mucinous differentiation was divided into four types, namely pure mucinous carcinoma, intraductal papillary mucinous carcinoma, signet ring cell type mucinous carcinoma, and mixed cell type mucinous carcinoma. Based on the macroscopic types according to Bormann's classification, pure mucinous carcinoma was mostly Type I, intraductal papillary mucinous carcinoma was mostly Type II, signet ring cell type mucinous carcinoma was mostly Type IV, and mixed cell type mucinous carcinoma was mostly Type III. The 5-year survival rate was 69.2, 64.2, 0, and 31.5%, respectively. There was a statistical difference in the lymph node metastasis rate and survival rate of the four carcinoma types. The invasion features of pure mucinous carcinoma entailed penetrating corrosively in a push-in form, without blood vessel or lymphatic metastasis and with few lymphocytes and lymphatic nodules in the marginal area. Thus, there was little lymph node metastasis and invasion of nerves. The HER2 protein expression rate was 40.2% (76/189), the HER2 gene amplification detected by FISH technology was 16.9% (32/189). Conclusion The independent histological type, four subtypes, and histopathological classification of gastric mucinous adenocarcinoma are important for the prognosis evaluation and precise treatment of this disease.